2019
DOI: 10.21203/rs.2.19276/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A qualitative study on caregivers and patients perceptions about Alzheimer’s and related dementias in southwestern Uganda

Abstract: BackgroundIn the treatment and safe service delivery of each disease, it is very important to understand the perceptions of caregivers and patients where they are not well understood because different cultures, regions and ethnicities have different ways how they understand the concept therefore this study aimed at understanding how patients and caregivers perceive Alzheimer’s and related dementias and their coping strategies in south western Uganda.Methods A qualitative cross sectional study was conducted usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The opting out of hospital use for non-formal care setting like places of religious worship was a consequence of several factors including knowledge gap on the disease. The study found that 76% of the caregivers attributed the disease to normal aging process, a scenario that has been reported in various studies including a parallel study done in the same area of Southwestern Uganda on caregivers and patients perceptions about Alzheimer's and related dementias [26]. Other studies have also documented this knowledge gap on the disease in other countries including the neibouring Tanzania [21] and the USA [27].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The opting out of hospital use for non-formal care setting like places of religious worship was a consequence of several factors including knowledge gap on the disease. The study found that 76% of the caregivers attributed the disease to normal aging process, a scenario that has been reported in various studies including a parallel study done in the same area of Southwestern Uganda on caregivers and patients perceptions about Alzheimer's and related dementias [26]. Other studies have also documented this knowledge gap on the disease in other countries including the neibouring Tanzania [21] and the USA [27].…”
Section: Discussionmentioning
confidence: 53%
“…Also the rare manner in which symptoms of dementia presented to the caregivers for example bad dreams, hallucinations, irrational talks, etc., resembled demonic attacks [28], and so caused them opt for spiritual prayers or traditional healers. Such people's belief in spiritual healing has been reported in several countries both developed and developing world [26,29,30]. Similarly, the explosion of Pentecostal churches and other prayer warriors in sub-Saharan Africa or in populations of African descent has made religious healing one of the most popular interventions for psychiatric and neurologic disorders [28] and emotional support [31].…”
Section: Discussionmentioning
confidence: 95%
“…The opting out of hospital use for non-formal care setting like places of religious worship was a consequence of several factors including knowledge gap on the disease. The study found that 76% of the caregivers attributed the disease to normal aging process, a scenario that has been reported in various studies including a parallel study done in the same area of Southwestern Uganda on caregivers and patients perceptions about Alzheimer's and related dementias (Tumuhairwe et al, 2020). Other studies have also documented this knowledge gap on the disease in other countries including the neibouring Tanzania (Hindley et al, 2017) and the USA (Beard, 2004).…”
Section: Discussionmentioning
confidence: 53%
“…Also the rare manner in which symptoms of dementia presented to the caregivers for example bad dreams, hallucinations, irrational talks, etc., resembled demonic attacks (Uwakwe, 2000), and so caused them opt for spiritual prayers or traditional healers. Such people's belief in spiritual healing has been reported in several countries both developed and developing world (Charan et al, 2018, Hamilton et al, 2019, Tumuhairwe et al, 2020. Similarly, the explosion of Pentecostal churches and other prayer warriors in sub-Saharan Africa or in populations of African descent has made religious healing one of the most popular interventions for psychiatric and neurologic disorders (Uwakwe, 2000) and emotional support (Lynn et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation